Reproductive Parameters of the Dogo Argentino Bitch - Caffaratti, Marina (2013)
The Dogo Argentino (DA) is the first and only breed from Argentina recognized worldwide. Although its morphologic features have been well established, its normal reproductive parameters are not clearly known. The aim of this study was to determine the main DA bitch reproductive parameters. One hundred and forty-nine surveys were obtained from breeders from C´ ordoba province, Argentina: one for each intact DA bitch from 1 to 14 years old. The DA bitch reached puberty at an average of 8.93 months. The mean duration of vulval bleeding found in this study was 11.11 days. The clinical signs characteristic for proestrous-estrous were vulval edema (89.93%), bleeding during the time of mating (32.21%), holding the tail to the side (95.30%), and docility during mating (85.91%). DA bitches had a whelping rate of 84%. Out of 299 pregnancies, 89.30% exhibited a normal parturition, 6.69% presented dystocia, 2.68% needed Cesarean section, and 1.34% aborted. In conclusion, the reproductive parameters of the DA bitch are similar to those identified for other large breeds. DA often showed a prolonged vulval bleeding longer than proestrus. Its high whelping rate, its low incidence of dystocia, and its good maternal ability define the DA as a good reproductive breed with normal reproductive functions.